2011
DOI: 10.1021/bi2012299
|View full text |Cite
|
Sign up to set email alerts
|

(S)-Styryl-α-alanine Used To Probe the Intermolecular Mechanism of an Intramolecular MIO-Aminomutase

Abstract: A Taxus canadensis phenylalanine aminomutase (TcPAM) catalyzes the isomerization of (S)-α- to (R)-β-phenylalanine, making (E)-cinnamate (~10%) as a byproduct at steady state. A currently accepted mechanism for TcPAM suggests that the amino group is transferred from the substrate to a prosthetic group comprised of an amino acid triad in the active site and then principally rebinds to the carbon skeleton of the cinnamate intermediate to complete the α-β isomerization. In contrast, when (S)-styryl-α-alanine is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…It was already shown that phenylalanine 2,3-aminomutase from Taxus canadensis (TcaPAM) could transform (S)α-styrylalanine (L-1a) into (2E,4E)-5-phenylpenta-2,4-dienoic acid (2a) as the major product. 28 Considering the high structural and sequence similarities between TcaPAM and PcPAL, it seemed commendable to explore the potential of PcPAL in the kinetic resolution of α-styrylalanines and stereoselective amination of (2E,4E)-styrylacrylates in the reverse reaction (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…It was already shown that phenylalanine 2,3-aminomutase from Taxus canadensis (TcaPAM) could transform (S)α-styrylalanine (L-1a) into (2E,4E)-5-phenylpenta-2,4-dienoic acid (2a) as the major product. 28 Considering the high structural and sequence similarities between TcaPAM and PcPAL, it seemed commendable to explore the potential of PcPAL in the kinetic resolution of α-styrylalanines and stereoselective amination of (2E,4E)-styrylacrylates in the reverse reaction (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic and structural characterizations of the MIO-containing aminomutases as a family have unveiled much unique chemistry, enzymology, and structural biology (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and exploitation of these enzymes as biocatalysts has provided access to α-and β-amino acids, which are difficult to prepare by other means (4,37). However, ʟ-phenylalanine and ʟ-tyrosine remain the only two known natural substrates (3)(4)(5).…”
Section: ·Smentioning
confidence: 99%
“…The MIO-containing aminomutases have been exploited as biocatalysts to generate novel α-and β-amino acids (8,37). SgcC4 exhibits substrate promiscuity, including L-dopa and L-3-chlorotyrosine, albeit with significantly reduced activity (8).…”
Section: ·Smentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] A PAM-like enzyme is also proposed to form part of the biosynthesis of the fungal toxin cyclochlorotine in Talaromyces islandisum based on identification of a candidate predicted open reading frame within the biosynthetic gene cluster. [5] The lack of characterisation with this class of enzyme is surprising given the detailed structural and biochemical knowledge of known enzymes [6][7][8][9][10] and the wealth of organisms shown to produce βphenylalanine-containing compounds. [2,[11][12][13][14] Progress in this area is likely hindered by the poor quality of enzyme sequence annotations in biological databases a fact which itself precludes correct identification biosynthetic pathways for known and novel bioactive molecules applicable to medical research.…”
Section: Introductionmentioning
confidence: 99%